(untitled) (Economics and region, 2019)
The problem of increasing the level of information security of the national economy is actualized in the article. Scientific approaches to the concept of "information security of the national economy" are systematized. The dual impact of digitization on the emergence of opportunities and threats to the functioning of the national economy is substantiated, which necessitates the development of tools to improve the level of reliability of economic information. The state of information security in modern computer systems of economic data processing is analyzed; requirements and directions of development of highly reliable computer systems for processing of economic data are substantiated. New scientific and scientific and technical achievements in the field of developing an optimal data backup in the economic sphere were obtained with the use of the non-positioned numerical system in residual classes, which improves the security and reliability of information processing.